Correction: DNA Damage, Homology-Directed Repair, and DNA Methylation. - Concetta Cuozzo; Antonio Porcellini; Tiziana Angrisano; Annalisa Morano; Bongyong Lee; Alba Di Pardo; Samantha Messina; Rodolfo Iuliano; Alfredo Fusco; Maria R Santillo; Mark T Muller; Lorenzo Chiariotti; et al. (PLoS Genetics)
[This corrects the article DOI: 10.1371/journal.pgen.0030110.].